Product Branding Training Model for MSMEs in Probolinggo Regency - Fauzan Muttaqien; Riza Bahtiar Sulistyan (Innovation Business Management and Accounting Journal, 2022)
In general, MSMEs play an important role in the era of globalization to support the rise of the Indonesian economy, especially during the COVID-19 pandemic. The impact of the Covid-19 case has affected life in terms of health, education, and economy. The number of COVID-19 cases that continues to grow has made the pace of business slow down. Moreover, people are currently reducing activities outside the home such as vacations or shopping. The wheels of the economy slowed down, the market began to sluggish, turnover declined, as well as productivity. The government has also prepared a stimulus to help boost the economy and maintain purchasing power. The strategy that must be taken is to create product innovations based on needs in order to survive in the midst of a pandemic. In order to exist in the midst of global competition, MSMEs like it or not, ready or not, must be able to adapt, including improving product quality and having the courage to label products, because it is very important to know and learn product branding.